Effect of low-impact aerobic exercise on blood glucose reduction in patients with type 2 diabetes mellitus: A quasi-experimental study - Hanifah, Aisyah Dani; Yuniartika , Wachidah (Jurnal Keperawatan, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with increasing global prevalence. Regular physical activity is recommended as a non-pharmacological strategy to improve glycemic control among individuals with T2DM.Objectives: This study aimed to examine the effect of low-impact aerobic exercise on reducing random blood glucose levels among patients with type 2 diabetes mellitus.Methods: A quasi-experimental study with a pretest–posttest design without a control group was conducted among 36 individuals with T2DM in Jetis Village, Sukoharjo, Indonesia. Participants performed low-impact aerobic exercise 2–3 times per week for eight weeks. Random blood glucose levels were measured before and after the intervention using the Easy Touch GCU meter. Data were analyzed using the Shapiro–Wilk test for normality and the Wilcoxon signed-rank test to determine the effect of the intervention.Results: The mean random blood glucose level decreased from 257.31 ± 54.12 mg/dL before the intervention to 167.22 ± 34.51 mg/dL after the intervention. The Wilcoxon signed-rank test showed a statistically significant reduction in blood glucose levels following the exercise program (p = 0.001).Conclusion: Low-impact aerobic exercise significantly reduces blood glucose levels in patients with type 2 diabetes mellitus. This intervention may serve as an effective complementary strategy for glycemic control in community-based diabetes management programs.